2000
DOI: 10.1016/s1097-2765(00)80416-5
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand-Induced Extracellular Cleavage Regulates γ-Secretase-like Proteolytic Activation of Notch1

Abstract: Gamma-secretase-like proteolysis at site 3 (S3), within the transmembrane domain, releases the Notch intracellular domain (NICD) and activates CSL-mediated Notch signaling. S3 processing occurs only in response to ligand binding; however, the molecular basis of this regulation is unknown. Here we demonstrate that ligand binding facilitates cleavage at a novel site (S2), within the extracellular juxtamembrane region, which serves to release ectodomain repression of NICD production. Cleavage at S2 generates a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
680
4
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 796 publications
(711 citation statements)
references
References 53 publications
16
680
4
1
Order By: Relevance
“…The requirement for ligand-dependent processing for Notch activity was verified using mutants disabled for interactions with ligand. The recombinant Notch1 LNG , which lacks the epidermal growth factor (EGF)-like repeats in its extracellular domain, 20 did not block death (Figure 2b), whereas a construct corrected for this defect (Notch1 LNG CCbSS ) imparted Figure 1 Characterization of the apoptotic response to neglect in HeLa cells. (a) Confocal image of HeLa cells cultured in complete medium (CM; nutrient replete) or buffered saline (neglect).…”
Section: Resultsmentioning
confidence: 99%
“…The requirement for ligand-dependent processing for Notch activity was verified using mutants disabled for interactions with ligand. The recombinant Notch1 LNG , which lacks the epidermal growth factor (EGF)-like repeats in its extracellular domain, 20 did not block death (Figure 2b), whereas a construct corrected for this defect (Notch1 LNG CCbSS ) imparted Figure 1 Characterization of the apoptotic response to neglect in HeLa cells. (a) Confocal image of HeLa cells cultured in complete medium (CM; nutrient replete) or buffered saline (neglect).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work demonstrated that EGF11 and EGF12 are the required elements for Notch1 to be able to recognize its ligands Jagged and DLL 15. Ligand binding leads to the cleavage at the juxtamembrane region (site S2) of Notch by ADAM (a disintegrin and metalloprotease) protease 16, 17. Shedding of the Notch extracellular domain facilitates subsequent intramembranous cleavage of Notch by γ ‐secretase complex, generating Notch intracellular domain (NICD or ICN)18, 19.…”
Section: Notch Signalingmentioning
confidence: 99%
“…Activation PS-RIP of several type I membrane receptors such as Notch and ErbB4 is regulated by ligand stimulation (Brou et al, 2000;Mumm et al, 2000;Ni et al, 2001). Therefore, we cotreated MDCK cells with a proteasome and ␥-secretase inhibitors to stabilize Met-CTF and stimulated the cells with HGF/SF ( Figure 5A).…”
Section: Sequential Proteolysis Of Met Is Independent Of Kinasementioning
confidence: 99%